Industry Financial Condition: On The Impact Of Stock Prices - Paramitha, Diky (STIE AMKOP, 2024)
The problem of declining industrial GDP in the period 2015 to 2021 has an impact on the financial performance of industrial companies. This study was conducted to test financial performance represented by the ratio of ROA, DER, and CR to stock prices in 10 sample industrial companies listed on the Indonesia Stock Exchange in the 2015-2021 period. The data used are secondary data of financial statements published using the purpose sampling method with a quantitative approach and the data tested using E-Views 13. The results showed that simultaneously the financial performance represented by ROA, DER, and CR did not affect the stock price of the industrial companies that were the research sample. Partially, only DER has an effect on the stock price, while ROA and CR have no effect. So it is concluded that stock price movements are not only determined by financial performance conditions but other fundamental factors need further research